Dispersal of the Invasive Pasture Pest Heteronychus arator into Areas of Low Population Density: Effects of Sex and Season, and Implications for Pest Management - Mansfield, Sarah; Gerard, Philippa J.; Hurst, Mark R. H.; Townsend, Richard J.; Wilson, Derrick J.; van Koten, Chikako (Frontiers in Plant Science, 2016)
African black beetle, Heteronychus arator (Scarabaeidae), is an exotic pest of pastures in northern New Zealand. Both adults and larvae feed on pasture grasses. Adults disperse by walking (short range) or flying (long range). Dispersal flights are triggered by warm night temperatures in spring and autumn. Short range adult dispersal in search of mates, food or oviposition sites is poorly understood. This study investigated walking activity of H. arator adults over three seasons in New Zealand pastures. Adult walking activity was monitored using pitfall traps along fence lines and in pasture plots on a dairy farm in Waikato, New Zealand, in spring 2013, spring 2014 and autumn 2015. Beetle populations were reduced by application of a biopesticide bait to compare walking activity between treated and control plots for up to 26 days post-treatment. Marked beetles were released into the pasture plots to measure the distance travelled by recaptured individuals. Trap catches along the fence lines were correlated with air temperatures in 2013. Trap catches were male biased in spring 2014 compared with autumn 2015. Trap numbers in the control plots were nearly double that of treated plots in both seasons. More beetles were caught in the pitfall traps at the edges of the treated plots than in the centre. Trap catches were consistent throughout the control plot in spring 2014, but in autumn 2015 more beetles were caught in the centre of the control plot than at the edges. Few marked beetles were recaptured with dispersal rates estimated as <0.5m per day. Warmer temperatures encouraged short range dispersal in H. arator. Males were more active than females during the spring mating season. Edge effects were strong and should be considered in the design of field experiments.